Analisis Peran dan Fungsi DPR/DPRD Sebagai Legislator ditinjau dari Perspektif Filsafat Hukum - Sucipto, Friska (Fakultas Hukum Universitas PGRI Kanjuruhan Malang, 2020)
Indonesia is a country that adheres to the Pancasila democracy system. State sovereignty is entirely in the hands of the people and is exercised according to the Constitution, as stipulated in Article 1 paragraph (2) of the 1945 Constitution. One of them is the representative institution of state administrators, namely the DPR / DPRD, one of which has the task of forming Legislations in accordance with the goals and ideals of the nation and reflecting justice that lives in society, in order to optimize the realization of the formation of good Prevailing Laws, a member DPR / DPRD must be a person with legal philosophy and understand more deeply about law and know good law for the people of Indonesia. Keywords: DPR / DPRD